2008
DOI: 10.1140/epjc/s10052-008-0585-7
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the mass and width of the W boson in e+e- collisions at $\sqrt{s}$ = 161–209 GeV

Abstract: A measurement of the W boson mass and width has been performed by the Delphi collaboration using the data collected during the full LEP2 programme (1996)(1997)(1998)(1999)(2000). The data sample has an integrated luminosity of 660 pb −1 and was collected over a range of centre-of-mass energies from 161 to 209 GeV. Results are obtained by applying the method of direct reconstruction of the mass of the W from its decay products in both the W + W − → ℓν ℓ qq ′ and W + W − → qq ′q q ′ channels. The W mass result f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 59 publications
0
27
0
Order By: Relevance
“…The first factor above represents the likelihood for the kinematic fit with that combination of jets, while the second factor reflects the degree of compatibility with the observed b-tagging assignments: 6) where the index j runs over all jets considered in the fit, and the probabilities p j equal ε l , (1 − ε l ), ε b , or (1 − ε b ), depending on the flavor assigned to each jet, and whether the jet is b-tagged. The b-tag efficiency (ε b ) is 60.6 ± 2.5%, and is calculated from tt simulation using the scale factors between data and simulation and the corresponding uncertainties from ref.…”
Section: The Ideogram Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first factor above represents the likelihood for the kinematic fit with that combination of jets, while the second factor reflects the degree of compatibility with the observed b-tagging assignments: 6) where the index j runs over all jets considered in the fit, and the probabilities p j equal ε l , (1 − ε l ), ε b , or (1 − ε b ), depending on the flavor assigned to each jet, and whether the jet is b-tagged. The b-tag efficiency (ε b ) is 60.6 ± 2.5%, and is calculated from tt simulation using the scale factors between data and simulation and the corresponding uncertainties from ref.…”
Section: The Ideogram Methodsmentioning
confidence: 99%
“…The data are split into − and + samples that contain, respectively, three-jet decays of the associated top or antitop quarks. For each event category, the Ideogram likelihood method [6] is used to measure the mass of the top quark (m t ) or antitop quark (m t ), and the difference between the masses in the two categories of lepton charge is taken as the mass difference ∆m t ≡ m t − m t . The Ideogram method was used previously [7,8] to measure the mass of the top quark.…”
Section: Introduction and Overviewmentioning
confidence: 99%
“…Additional tests were performed in the fully hadronic final state using mixed Lorentz-boosted Z events [51], in which W W events are emulated using two events taken at the Z peak, and transforming them such that their superposition reflects that of a true fully hadronic W W event. These studies are also sensitive to systematic errors in the event reconstruction technique, and are discussed further in the relevant section below.…”
Section: Modelling Of Fragmentationmentioning
confidence: 99%
“…An additional problem, not included in the effects considered above, has been encountered in the reconstruction of charged tracks in the forward region of DELPHI [51], leading to a small error in the reconstructed direction of forward tracks in both simulated and real data. Its effects were shown to be negligible in a previous DELPHI analysis [6] involving fits to binned data of production and decay distributions in W W production, and, in a study of the current data in the jj ν final state at 200 GeV, have also been found to be negligible in comparison to the other correlated systematic errors considered.…”
Section: Event Reconstructionmentioning
confidence: 99%
“…Improving the measurement of M W is an important contribution to our understanding of the electroweak (EW) interaction, and, potentially, of how the electroweak symmetry is broken. The current world-average measured value is M W ¼ 80:399 AE 0:025 GeV [1] from a combination of measurements from the ALEPH [2], DELPHI [3], L3 [4], OPAL [5], D0 [6], and CDF [7,8] Collaborations.…”
mentioning
confidence: 99%